Replication and meta‐analysis of common variants identifies a genome‐wide significant locus in migraine. Issue 5 (7th January 2013) - Esserlind, A.‐L.; Christensen, A. F.; Le, H.; Kirchmann, M.; Hauge, A. W.; Toyserkani, N. M.; Hansen, T.; Grarup, N.; Werge, T.; Steinberg, S.; Bettella, F.; Stefansson, H.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Genetic factors contribute to the aetiology of the prevalent form of migraine without aura (MO) and migraine with typical aura (MTA). Due to the complex inheritance of MO and MTA, the genetic background is still not fully established. In a population‐based genome‐wide association study by Chasman et al. (Nat Genet 2011: 43: 695–698), three common variants were found to confer risk of migraine at a genome‐wide significant level (P < 5 × 10−8). We aimed to evaluate the top association single nucleotide polymorphisms (SNPs) from the discovery set by Chasman et al. in a primarily clinic‐based Danish and Icelandic cohort. Methods The top association SNPs were assessed in 2523 cases and 38 170 controls, and a meta‐analysis was performed, combining the discovery set with all the follow‐up studies. Finally the confirmed SNPs were assessed in a genotype–phenotype analysis. Results Two out of three SNPs that showed genome‐wide significant associations in the previous study: rs10166942 (near TRPM8) and rs11172113 (in LRP1) were significantly associated with migraine in the present study. The meta‐analysis confirmed the previous three genome‐wide significant associated SNPs (rs2651899, rs10166942 and rs11172113) to confer risk of migraine. In addition, the C‐allele of rs2078371 (near TSPAN‐2) also reached genome‐wide significance for association with migraine [OR = 1.14; CI = (1.09–1.20); P = 2.55 × 10−8]. Conclusion TSPAN‐2 encodes an integral membrane protein involved in oligodendrogenesis. This new finding supports the plausible implication of neuroglia in the pathophysiology of MO and MTA.